Just action : how to challenge segregation enacted under the color of law - Rothstein, Richard; Rothstein, Leah (Liveright Publishing Corporation, 2023)
The Color of Law brilliantly recounted how government at all levels created segregation. Just Action describes how we can begin to undo it.